2022
DOI: 10.15644/asc56/2/2
|View full text |Cite
|
Sign up to set email alerts
|

Dental Status and Periodontal Health of Patients with Phenylketonuria in Latvia

Abstract: Objectives Phenylketonuria (PKU) is an autosomal recessive inherited disorder of phenylalanine metabolism resulting from a deficiency of phenylalanine hydroxylase. The aim of this study was to evaluate the dental status and periodontal health of PKU patients in Latvia. Material and Methods Forty-five PKU patients and age/sex-matched controls were recruited for this cross-sectional study. Their anamnestic data, periodontal health and dental status were assessed by one ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, there are various studies that show that patients with PKU have more oral complications than normal ones. For example, Ābola et al 17 reported that the dental status and periodontal health of PKU patients were found to be significantly inferior compared to healthy controls associated with the regular consumption of PKU formula and the difficulties which mentally and/or physically disabled PKU patients experience with their oral hygiene. But there is a big difference with our study, we have performed a study on children with ages around 4 years while the median age of people in Ābola et al 17 study was 22 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are various studies that show that patients with PKU have more oral complications than normal ones. For example, Ābola et al 17 reported that the dental status and periodontal health of PKU patients were found to be significantly inferior compared to healthy controls associated with the regular consumption of PKU formula and the difficulties which mentally and/or physically disabled PKU patients experience with their oral hygiene. But there is a big difference with our study, we have performed a study on children with ages around 4 years while the median age of people in Ābola et al 17 study was 22 years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ābola et al 17 reported that the dental status and periodontal health of PKU patients were found to be significantly inferior compared to healthy controls associated with the regular consumption of PKU formula and the difficulties which mentally and/or physically disabled PKU patients experience with their oral hygiene. But there is a big difference with our study, we have performed a study on children with ages around 4 years while the median age of people in Ābola et al 17 study was 22 years. On the other hand, Ballikaya et al 7 reported that 67% of PKU patients have dental caries, but they also mentioned that of the patients, 85.3% did not brush their teeth regularly and 90.4% had never visited a dentist before, which makes the conclusion ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Upon examination of the dental status and periodontal health examination of PKU patients in Latvia, a notable observation surfaced, revealing that an overwhelming majority (93%) need professional dental cleaning performed by a dental hygienist [5].…”
Section: Discussionmentioning
confidence: 99%
“…PKU patients need to be recommended to rinse their mouth with water immediately after consuming the PKU formula to counteract the acidity in their oral cavity [5]. An increased acidity in the oral cavity too often or for prolonged periods of time results in the demineralisation of tooth structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation